Styphnolobium japonicum (L.) Schott fruits increase stress resistance and exert antioxidant properties in Caenorhabditis elegans and mouse models - Thabit, Sara; Handoussa, Heba; Roxo, Mariana; Cestari de Azevedo, Bruna; S. E. El Sayed, Nesrine; Wink, Michael (Molecules, 2019)
Styphnolobium japonicum (L.) Schott is a popular Asian tree widely used in traditional medicine. The current study explored the potential stress resistance and antioxidant activities of its fruits. Phytochemical profiling of the hydroalcoholic fruit extract was done via high performance liquid chromatography-photodiode array-electrospray ionization-mass/mass (HPLC-PDA-ESI-MS/MS). Twenty four phenolic constituents were tentatively identified in the extract. The Caenorhabditis elegans (C. elegans) nematode model in addition to trimethyltin (TMT)-induced neurotoxicity mouse model were used for in vivo evaluation of its antioxidant properties. The ability of the extract to enhance stress resistance was manifested through increasing survival rate by 44.7% and decreasing basal reactive oxygen species (ROS) levels by 72.3% in C. elegans. In addition, the extract increased the levels of the stress response enzyme superoxide dismutase-3 (Sod-3) by 55.5% and decreased the expression of heat shock protein-16.2 (Hsp-16.2) in nematodes, which had been challenged by juglone, by 21%. Using a mouse model, the extract significantly decreased the expression of the oxidative stress marker malondialdehyde (MDA). Furthermore, an elevation in the levels of the antioxidant marker glutathione (GSH), SOD and heme oxygenase-1 (HO-1) enzymes were observed. Our findings imply that Styphnolobium japonicum has the potential to be used in future studies focusing on diseases associated with oxidative stress.
Gesehen am 17.10.2019